Hubungan Genetik, Kebiasaan Merokok, dan Aktivitas Fisik dengan Kejadian Diabetes Melitus Tipe 2 pada Lansia di Wilayah Kerja Puskesmas Sikumana Tahun 2021 - Lidya Evangelita Clara Taja; Honey Ivon Ndoen; Helga J. N. Ndun (Yayasan Literasi Sains Indonesia, 2024)
Diabetes mellitus is the chronic illness knows as brought on by insufficient insulin production by the pancreas. As people age and lead increasingly unhealthy lifestyle, type 2 diabetes melitus becomes more common. The prevalence of type 2 diabetes mellitus in East Nusa Tenggara is 20.599 sufferers, and almost 30% of sufferers have not received health services. Diabetes mellitus at the Sikumana Health Center is in second place, with 4.214 sufferers based on the number of visits. The aims of this research how to know the association between family history, smoking behaviors, and physical activity with the incidence of type 2 diabetes mellitus in the elderly in the Sikumana Community Health Center working area in 2021. The type of research was a quantitative study with a case control design. The case population in this study were all diabetes mellitus sufferers in aged 60-80 years and were recorded in the medical records, while the control population in this study were those who were not diabetes mellitus sufferers who were recorded in the medical records and a sample consisted of 88 people and these samples was taken using simple random sampling. Data were analyzed using a chi-square statistical test. The results showed that there was a relationship between family history (p=0.009) and physical activity (p=0.001) with the incidence of diabetes mellitus in the elderly in the working area of the Sikumana Health Center, while smoking habits (p=0.483) there is no relationship with the incidence of diabetes mellitus in the elderly in the working area of the Sikumana Health Center.